2020
DOI: 10.1108/ijotb-08-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and citizenship behavior

Abstract: PurposeThe purpose of this study is to assess the pathway through which authentic leadership influences organizational citizenship behavior (OCB). The authors examine how the perception of overall fairness and a sense of belongingness mediate the relationship between authentic leadership and OCB.Design/methodology/approachThe authors distributed survey questionnaires to full-time employees working for an insurance company. Data were collected in two phases. To test the hypotheses, the authors conducted hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…When employees experience positive exchanges in the organizational environment which leave a positive perception, organizational citizenship behavior tends to ensue. Past studies have confirmed that employees who experience psychological empowerment (Turnipseed and VandeWaa, 2020) and overall fairness (Kyei-Poku and Yang, 2020) tend to engage in organizational citizenship behaviors beyond their in-role responsibilities. A framework detailing the antecedents and consequences of the internal reputation concept is shown in Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…When employees experience positive exchanges in the organizational environment which leave a positive perception, organizational citizenship behavior tends to ensue. Past studies have confirmed that employees who experience psychological empowerment (Turnipseed and VandeWaa, 2020) and overall fairness (Kyei-Poku and Yang, 2020) tend to engage in organizational citizenship behaviors beyond their in-role responsibilities. A framework detailing the antecedents and consequences of the internal reputation concept is shown in Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…Ethical fairness is an important virtue in an authentic leader. This is closely related to ethics and moral components (Kyei-Poku and Yang, 2020). Self-awareness is about positivity and optimism to make efficient decisions that are associated with self-awareness.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the two separate elements of internal regulation and strong moral views are merged to produce an individual's moral viewpoint component (Gardner et al, 2005). Numerous studies have devoted to the various outcomes correlated with greater levels of subordinate trust in the leader, involvement, workplace well-being, such as continuous improvement (Gardner et al, 2005), effectiveness (Nasab & Afshari, 2019), trust (Clapp-Smith et al, 2009, employee organizational citizenship behavior (Kyei-Poku & Yang, 2020).…”
Section: Adriel Analynmentioning
confidence: 99%